ASAL PENAMAAN DUSUN-DUSUN DI KELURAHAN BANYURADEN: PERSPEKTIF LINGUISTIK DAN SEJARAH - Andrianie Lisa; Sudartomo Macaryus (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to describe the grouping, formation process, and meaning of the origin of the naming of hamlets in the Banyuraden Village. This type of research is descriptive qualitative. The analytical method is in the form of the Spradley ethnographic method, the distribution method. Cultural theme analysis technique, the basic technique for Direct Elements (BUL). The method is presented formally and informally. The results of this study are (1) Grouping the origin of naming namely the origin of the word, the origin of history, and origin of language (2) The process of forming the origin of the naming is zero derivation, affixation, abreviation, and composition. (3) The meaning of naming includes lexical meaning, grammatical meaning, and cultural meaning.